Pengaruh Modal Usaha dan Tenaga Kerja Terhadap Output IKM Pangan Minyak Kelapa di Provinsi Gorontalo - Amelia Yunus; Irawati Abdul; Ivan R. Santoso (Masyarakat Ekonomi Syariah Bogor, 2025)
This research examines the influence of business capital and labor on the output of Small and Medium Industries (IKM) in the coconut oil food sector in Gorontalo Province. The main focus is directed at the contribution of business capital assistance provided by the regional government since 2021. The research uses panel data from 70 IKM assisted by the Gorontalo Province Department of Cooperatives, SMEs, Industry and Trade during the 2018–2023 period. The analysis was carried out using the multiple linear regression method using the Random Effect Model approach, which was determined based on the Chow, Hausman and Lagrange Multiplier tests. The estimation results show that business capital has a positive and significant effect on SME output, while labor has a positive but not significant effect on output. These findings have the implication that government intervention in the form of capital assistance contributes significantly to increasing SME output, and its effectiveness can be strengthened through improving the quality of the workforce.